2018
DOI: 10.1186/s13046-018-0717-3
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: MicroRNA-1468 promotes tumor progression by activating PPAR-γ-mediated AKT signaling in human hepatocellular carcinoma

Abstract: BackgroundAccumulating evidence confirm that aberrant microRNAs (miRNAs) expression contributes to hepatocellular carcinoma (HCC) development and progression. Previous study reported that miR-1468 showed an up-regulated tendency and might be a potential prognostic biomarker in HCC samples derived from TCGA database. However, the role of miR-1468 and its underlying mechanisms involved in the growth and metastasis of HCC remain poorly investigated.MethodsCCK-8, EdU, colony formation and flow cytometry were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 40 publications
(49 reference statements)
1
58
0
Order By: Relevance
“…Previous studies have demonstrated that the loss or gain of miRNA function is implicated in the tumourigenesis and progression of HCC via modulating the expression of oncogenes or tumour suppressor genes . Our group has recognized several miRNAs as regulators in the growth and metastasis of HCC, such as miR‐187‐3p, miR‐1468, miR‐23c, miR‐671‐5p and miR‐204 . In the current study, we identified miR‐627‐5p as a novel tumour suppressor in HCC.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Previous studies have demonstrated that the loss or gain of miRNA function is implicated in the tumourigenesis and progression of HCC via modulating the expression of oncogenes or tumour suppressor genes . Our group has recognized several miRNAs as regulators in the growth and metastasis of HCC, such as miR‐187‐3p, miR‐1468, miR‐23c, miR‐671‐5p and miR‐204 . In the current study, we identified miR‐627‐5p as a novel tumour suppressor in HCC.…”
Section: Discussionmentioning
confidence: 53%
“…MiRNAs have been identified as critical suppressors or drivers in the development and progression of human cancer . In HCC, our group has recognized several oncogenic or tumour suppressive miRNAs, which are implicated in tumour growth and metastasis . For instance, miR‐1468 acts as a tumour promoting factor by targeting Cbp/p300 interacting transactivator with Glu/Asp rich carboxy‐terminal domain 2 (CITED2) and Up‐frameshift protein 1 (UPF1) in HCC .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating studies have found that miRNAs are aberrantly expressed and dysfunctional in HCC . Recently, miRNAs have been shown to be associated with diagnosis, development, progression and prognosis of human HCC . miR‐301b‐3p is recently recognized as a cancer‐related miRNA.…”
Section: Introductionmentioning
confidence: 99%
“…This miRNA has been implicated in different cancer types [36, 37] and the latter pathway may indicate a potential mechanism for this. In fact, MIR1468 was recently shown to promote tumor progression by activating PPAR- γ -mediated Akt signaling in hepatocellular carcinoma [38].…”
Section: Resultsmentioning
confidence: 99%